Awareness regarding clinical application of pharmacogenetics among Japanese pharmacists - Obara T; Abe S; Satoh M; Gutiérrez Ubeda SR; Yoshimachi S; Goto T (Dove Medical Press, 2015)
Taku Obara,1–3 Shinya Abe,4 Michihiro Satoh,1 Sergio Ramón Gutiérrez Ubeda,5 Shoko Yoshimachi,4 Teruaki Goto4 1Department of Pharmacy, Tohoku University Hospital, Sendai, 2Division of Molecular Epidemiology, Environment and Genome Research Center, Tohoku University Graduate School of Medicine, Sendai, 3Department of Preventive Medicine and Epidemiology, Tohoku Medical Megabank Organization, Tohoku University, Sendai, 4Tsuruha Holdings, Sapporo, 5Department of Geriatric Behavioral Neurology, Tohoku University Graduate School of Medicine, Sendai, Japan Abstract: Advances in pharmacogenetic analysis technology have accelerated the movement to incorporate pharmacogenetic analysis data into medicine. Therefore, pharmacists will soon have to provide guidance and raise pharmaceutical questions regarding prescriptions based on patient pharmacogenomic information. The objective of this study was to clarify Japanese pharmacists' awareness of pharmacogenetics. We conducted a postal questionnaire survey among 372 pharmacists belonging to Tsuruha Holdings. Available data were collected from 268 pharmacists (male [n=133], <40 years old [n=170], drugstore pharmacists [n=182]). Of the pharmacists, 19.0% of the population were aware of the Ethical Guidelines for Human Genome/Gene Analysis Research in Japan, 31.0% of the population had heard either or both the terms “pharmacogenomics” and “pharmacogenetics”, and 16.8% of the population were aware that health insurance covered pharmacogenomic tests performed before prescription in Japan. Only 0.4% indicated that they could raise pharmaceutical questions regarding prescriptions based on patients' pharmacogenomic information, and 61.2% of the population indicated a preference to undertake pharmacogenomic tests to predict the efficacy or adverse reactions of a drug. We found a need for actions to improve the awareness of pharmacists about pharmacogenetics and create an environment in which pharmacists are able to provide appropriate medical service based on pharmacogenomic information. Keywords: pharmacogenomics/pharmacogenetics, awareness, pharmacist